The antlions of Cyprus: review and new reports (Neuroptera: Myrmeleontidae) - Badano, Davide; Makris, Christodoulos; John, Eddie; Hadjiconstantis, Michael; Sparrow, David; Sparrow, Rosalyn; Thomas, Bethan; Devetak, Dušan (Fragmenta entomologica, 2019)
The antlions (Myrmeleontidae) of Cyprus have been poorly studied and only 13 species were known from this biogeographically interesting island. In light of new field research, we provide an updated checklist to the Cypriot antlions, including seven species reported for the first time from the island. Of these, the findings of the Middle Eastern species Distoleon laticollis and Cueta kasyi are particularly noteworthy. The Cypriot antlion fauna appears dominated by widespread Mediterranean elements, with relatively few Middle Eastern and endemic species.